Changes in pentobarbital induced sleeping-time in mice infected with Schistosoma mansoni and immunosuppressed - Tonelli, Sônia Maria de Assis Fonseca; Brasileiro Filho, Geraldo; Goulart, Eugênio Marcos de Andrade; Coelho, Paulo Marcos Zech (Revista do Instituto de Medicina Tropical de São Paulo, 1995)
To evaluate whether the intensity of the hepatic granulomatous response induced by S. mansoni eggs plays a role in drug metabolism, mice were infected with 40 cercariae and tested to assess the sodic pentobarbital induced sleeping-time. To decrease the inflammatory reaction the animals were irradiated with 400 Rad or received azathioprine, 20mg/kg, 3 times a week, for 4 weeks, respectively in or beginning in the 33th post-infection day. In infected animals receiving azathioprine the area of the hepatic granulomas was smaller and the sleeping-time was similar to that of non-infected ones (controls). In mice infected and irradiated the granuloma dimensions were similar to those of animals only infected, in these two latter groups of animals, the sleeping-time was more prolonged than that of the control animals. These results show that: 1) mice with unaltered hepatic granulomatous reaction show reduction in metabolism of sodic pentobarbital; 2) granulomatous response diminished by azathioprine does not interfere with the capacity of metabolism of the anesthetic drug.